Exploring Factors of the Willingness to Accept AI-Assisted Learning Environments: An Empirical Investigation Based on the UTAUT Model and Perceived Risk Theory - Wu, Wentao; Zhang, Ben; Li, Shuting; Liu, Hehai (Frontiers in Psychology, 2022)
Artificial Intelligence (AI) technology has been widely applied in many fields. AI-assisted learning environments have been implemented in classrooms to facilitate the innovation of pedagogical models. However, college students’ willingness to accept AI-assisted learning environments has been ignored. Exploring the factors that influence college students’ willingness to use AI can promote AI technology application in higher education. Based on the Unified Theory of Acceptance and Use of Technology (UTAUT) and the theory of perceived risk, this study identified six factors which influence students’ willingness to use AI to analyze their relationships with willingness to accept (WTA) AI-assisted learning environments. A model including six hypotheses was constructed to test the factors affecting students’ WTA. The results indicated that college students showed “weak rejection” of the construction of AI-assisted learning environments. Effort expectancy (EE), performance expectancy (PE), and social influence (SI) were all positively related to college students’ willingness to accept AI-assisted learning environments. Psychological risk (PR) significantly negatively influenced students’ WTA. The findings of this study will be helpful for carrying out risk communication, which can promote the construction of AI-assisted learning environments.